Pengaruh Strategi Pemasaran Terhadap Peningkatan Volume Penjualan Kayu Manis Pada PT. CV Rempah Sari Kota Padang - Hafiz Al Abrar; Melisa Putri; Bunga Henida Putri; Fitriyani Fitriyani; Ramdani Bayu Putra (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the influence of marketing strategy on sales volume in CV.Rempah Sari in Padang City by using segmenting, targeting, and positioning strategies both partially and simultaneously. marketing is one of the most important functions in the company, where with the right marketing it can determine the sales volume and the position of the company (product) in the market. The data collection technique used in this study is by using questionnaires or questionnaires, namely data collection techniques carried out by providing a set of questions or statements to the leadership of CV.Rempah Sari kota padang. The purpose of this research is to find out how the influence of marketing strategies on the increase in the sales volume of sweet skins in cv.spice sari kota padang. The results of this research show that CV.Rempah Sari has a quality marketing strategy that can meet the needs of consumers.